2011
DOI: 10.1093/infdis/jir543
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Factor Toxemia and Anti-Protective Antigen Antibody Activity in Naturally Acquired Cutaneous Anthrax

Abstract: Cutaneous anthrax outbreaks occurred in Bangladesh from August to October 2009. As part of the epidemiological response and to confirm anthrax diagnoses, serum samples were collected from suspected case patients with observed cutaneous lesions. Anthrax lethal factor (LF), anti-protective antigen (anti-PA) immunoglobulin G (IgG), and anthrax lethal toxin neutralization activity (TNA) levels were determined in acute and convalescent serum of 26 case patients with suspected cutaneous anthrax from the first and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…Unlike most infections with Vibrio cholerae and Clostridium difficile, infection with Bacillus anthracis is characterized by toxemia. Anthrax lethal factor has been measured in the blood from human cases of cutaneous anthrax, at concentrations up to 1.26 ng/ml (70), and in the blood and pleural fluid of humans and monkeys with inhalational anthrax, at concentrations of Ͼ500 ng/ml (71,72). Measurement of anthrax toxin levels in target organ tissues has not been reported and requires knowledge of the relevant target tissue and a tissue-specific method for toxin quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most infections with Vibrio cholerae and Clostridium difficile, infection with Bacillus anthracis is characterized by toxemia. Anthrax lethal factor has been measured in the blood from human cases of cutaneous anthrax, at concentrations up to 1.26 ng/ml (70), and in the blood and pleural fluid of humans and monkeys with inhalational anthrax, at concentrations of Ͼ500 ng/ml (71,72). Measurement of anthrax toxin levels in target organ tissues has not been reported and requires knowledge of the relevant target tissue and a tissue-specific method for toxin quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these functions require mechanotransduction at the micro-to millisecond scale, suggesting that the transducers are mechanosensitive ion channels (MSCs). This is confirmed by the recent discovery of genes responsible for our senses or touch (Ranade et al, 2014b), hearing (Pan et al, 2013), and proprioception (Boyer et al, 2011;Woo et al, 2015). Yet the genes responsible for our most unwanted experience of mechanotransduction, our sense of pain, remain elusive.…”
Section: Introductionmentioning
confidence: 95%
“…They rely on a cellular phenomenon called mechanotransduction, during which mechanical forces are converted into electrical signals. This vital process underlies several physiological functions such as hearing, touch, pain, and proprioception (Boyer et al, 2011;Chalfie, 2009;Li et al, 2012;Woo et al, 2015), as well as the myogenic tone of resistance arteries (Sharif-Naeini et al, 2009), fluid homeostasis and the sensation of thirst (Bourque, 2008;Zaelzer et al, 2015), and flow sensing in kidney tubules (Peyronnet et al, 2012). Many of these functions require mechanotransduction at the micro-to millisecond scale, suggesting that the transducers are mechanosensitive ion channels (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports also showed that anti-PA IgG enzyme-linked immunosorbent assay (ELISA) is a valuable tool for confirmation of cutaneous and inhalational anthrax cases (19). In a recent study, anti-PA IgG and anthrax lethal toxin neutralization activity levels were found to be very useful for detection and confirmation of natural cutaneous anthrax cases in Bangladesh (1).…”
mentioning
confidence: 99%